Mesobiotus philippinicus sp. nov., the first limnoterrestrial tardigrade from the Philippines - Mapalo, Marc A.; Stec, Daniel; Mirano-Bascos, Denise; Michalczyk, Łukasz (Zootaxa, 2016)
The limnoterrestrial tardigrade fauna of the Philippines is completely unknown. In this paper, we describe the first ever limnoterrestrial water bear species from this southeast Asian country, Mesobiotus philippinicus sp. nov., found in a moss sample collected in Quezon City. Apart from morphometrics and imaging in light microscopy, we also analysed the new species under scanning electron microscope and sequenced four DNA markers differing in mutation rates, three nuclear (18S rRNA, 28S rRNA, and ITS-2) and one mitochondrial (COI). This allowed not only a detailed description but also provided barcodes to aid future species identification. The new species belongs to the harmsworthi group and is most similar to M. diffusus (Binda & Pilato, 1987), M. pseudocoronatus (Pilato et al., 2006), M. montanus (Murray, 1910) and M. mottai (Binda & Pilato, 1994), but differs from these species by whorled egg processes and dimensions of some morphometric traits. The 28S rRNA, ITS-2 and COI sequences presented in this paper are the first published DNA sequences for the genus Mesobiotus.